Boveri at 100: Theodor Boveri and genetic predisposition to cancer1. Issue 2 (October 2014) - Hansford, Samantha; Huntsman, David G
Abstract One hundred years have passed since the publication of Theodore Boveri's Zur Frage der Entstehung maligner Tumouren [Concerning the Origin of Malignant Tumours]. This prescient publication created the foundations for much of our understanding of the origins of cancer and in particular the genetic basis of some cancers. In his work, Boveri suggested that loss of key cellular attributes, now known as tumour suppressor genes, are a key driver event in the development of cancer and inheritance could play a role in cancer susceptibility. He also predicted that chromosomal (genomic) instability as a key hallmark of cancer. Whilst these key insights that still inform the practice of cancer genetics, they were not the main theme of Boveri's text, which was to describe the role of chromosomal abnormalities in the development of cancer. In making his case he also suggested that genetic information could be contained in distinct packages (genes) that are linearly arranged along chromosomes and that cancers arise from single cells. These remarkably accurate hypotheses add weight to the need to celebrate this landmark publication for its accurate prediction of so much that we take for granted. Here we focus on Boveri's contributions to our understanding of hereditary cancers, which, alongside the astute clinical observations of Paul Broca and Aldred Scott Warthin, were published decades before the field became respectable, yet could still inform anyone studying hereditary cancers. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd